Cloudbursts of the Mid-Atlantic - Smith, James A.; Baeck, Mary Lynn; Miller, Andrew; Ryzhkov, Alexander; Hu, Jiaxi (AGU, 2025)
Extreme short-duration rainfall in the Mid-Atlantic region of the US is examined through polarimetric radar analyses of storms that produced rainfall accumulations exceeding 1,000-year values for time scales less than 3 hr. Polarimetric radar analyses of Mid-Atlantic cloudbursts focus on dynamical processes associated with updrafts and downdrafts, microphysical processes associated with extreme rainfall rates and mesoscale processes associated with structure, motion and evolution of convective systems over short time scales and small spatial scales. Dynamical processes associated with updrafts and downdrafts play a key role in determining the spatial and temporal distribution of extreme rainfall and in dictating errors in radar rainfall estimates through the effects of vertical motion. The microphysics of extreme short-duration rainfall exhibit a mix of cold and warm rain processes, with cold rain processes contributing to cycles of growth and decay in raindrop size distributions. Analyses are designed to address critical research problems linked to modernizing methods for estimating Probable Maximum Precipitation (PMP). Polarimetric radar provides an important path for estimating rainfall for PMP-magnitude storms. We compare rainfall analyses from recent storms in the Mid-Atlantic with cloudburst rainfall from the pre-radar era, including storms that produced record or near-record rainfall accumulations for the US and the world. Rainfall accumulations at time scales shorter than 3 hr for polarimetric era storms are large relative to rainfall frequency results, but modest in comparison with rainfall maxima from historical cloudbursts in the Mid-Atlantic.
Keywords: probable maximum precipitation; extreme events; hydrometeorology; floods